If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(x + 3) + 4(4x + -3) = 5(x + -6) + 12 Reorder the terms: -10(3 + x) + 4(4x + -3) = 5(x + -6) + 12 (3 * -10 + x * -10) + 4(4x + -3) = 5(x + -6) + 12 (-30 + -10x) + 4(4x + -3) = 5(x + -6) + 12 Reorder the terms: -30 + -10x + 4(-3 + 4x) = 5(x + -6) + 12 -30 + -10x + (-3 * 4 + 4x * 4) = 5(x + -6) + 12 -30 + -10x + (-12 + 16x) = 5(x + -6) + 12 Reorder the terms: -30 + -12 + -10x + 16x = 5(x + -6) + 12 Combine like terms: -30 + -12 = -42 -42 + -10x + 16x = 5(x + -6) + 12 Combine like terms: -10x + 16x = 6x -42 + 6x = 5(x + -6) + 12 Reorder the terms: -42 + 6x = 5(-6 + x) + 12 -42 + 6x = (-6 * 5 + x * 5) + 12 -42 + 6x = (-30 + 5x) + 12 Reorder the terms: -42 + 6x = -30 + 12 + 5x Combine like terms: -30 + 12 = -18 -42 + 6x = -18 + 5x Solving -42 + 6x = -18 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -42 + 6x + -5x = -18 + 5x + -5x Combine like terms: 6x + -5x = 1x -42 + 1x = -18 + 5x + -5x Combine like terms: 5x + -5x = 0 -42 + 1x = -18 + 0 -42 + 1x = -18 Add '42' to each side of the equation. -42 + 42 + 1x = -18 + 42 Combine like terms: -42 + 42 = 0 0 + 1x = -18 + 42 1x = -18 + 42 Combine like terms: -18 + 42 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| (30-b)*(30-b)+b*b=900 | | 5y+8=2y+2+(-3) | | 4(2x+5)-12= | | 3(1+103x)=5 | | 5(n-2)-(7-4n)=8n | | 5a+7b+12c=7a+10b+8c | | 3x^2-22x+1=0 | | -80cosx+40+40sinx=0 | | (x+4)2=54 | | 7(n-6)-(4-3n)=9n | | 5/e=3/4 | | -2X+18=-62 | | 5x-3y-1=0 | | 3/4=5/e | | y-5=-7/2(x-7) | | 1/7=n/10 | | 2X+18=62 | | 3(x-5)=-4x | | 3y+6-y=7+y-5 | | 0=-n+n | | 8n-8n=0 | | 1-9/4 | | 0=p+5+2 | | 6x+10-z=1+4z+4 | | c-9/4c | | 3sin^2x=5sinx+8 | | -2x-3x=-10 | | 5y+1-2y=7+2y+7 | | -4(5x+6)= | | 13u+9v-4u= | | 4z-8=5z-5 | | 2/3=8/9 |